EVALUATION OF CLINICAL EFFECTS OF OCCLUSAL TRAUMA ON GINGIVAL RECESSION - Mihaela Moisei; Cosmin Popa; Ioana Rudnic; Dana Popa; Amelia Surdu; Nicoleta Ioanid; Lucian Burlea; Silvia Martu (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study The aim of this study was to investigate the occlusal contacts during maximum intercuspation to protrusive, lateroprotrusive and lateral excursive movements and their effects on gingival recession. Material and methods Fourteen subjects having gingival recession aged by 18-53 years old were selected, examined about the location and extent of gingival recession and occlusal wear facets were recorded. The type of occlusion and the nature of occlusal contact in maximum intercuspation and eccentric mandibular movements were also recorded using articulating foil. Results Our results indicated that gingival recession was more frequent in patients with occlusal function group than at patients with occlusal canine protection. At patients with occlusal canine protection gingival recession was located on the labial surface while at patients with function group recession was equally distributed on vestibular surface of the teeth in the anterior and posterior areas. Almost all patients with interference in protrusive, lateroprotrusive movements had teeth with gingival recession. Also abrasion was observed in most teeth with gingival recession. Conclusions These results suggest that occlusal interferences in maximum intercuspation and eccentric movements in one form or the other and absence of mutually protected occlusion can contribute to gingival lesions such as gingival recessions.